Unraveling the capacitive effect in the vacancy-heterostructure WTe2/MoTe2 for hydrogen evolution reaction by the grand canonical potential kinetics. (1st August 2022) - Wang, Wugang; Kwon, Soonho; Xu, Lai; Goddard, William A.
Abstract: Heterostructure shows superior catalytic performance since it inherits the catalytic properties of the components, and has the advantages of van der Waals interaction. Herein, we build a vacancy-van der Waals heterostructure with MoTe2 and WTe2 which forms a capacitor tuning performance, playing an important role in the energy barrier balance of the catalytic reaction. By using the grand canonical reaction kinetics (GCP-K) to explore the electrocatalytic, we predict the Tafel slope of the HER reaction is 81.31 mV/dec through changing applied potential. Graphical abstract: Image 1 Highlights: We used van der Waals interaction to design a new vacancy-heterostructure system. We proposed a capacitor model which participates in the HER reaction. We used GCP-K to obtain the Tafel slope (81.31 mV/dec) which is closer to experiment than CHE method.